Semantic Development in Taiwan Mandarin-Speaking Children: A Study of V-Diao - Chun-Yin Doris Chen; Jheng-Syun Eliot Huang (Languages, 2025)
This study investigates the semantic development of V-diao in Taiwan Mandarin-speaking children, focusing on how they acquire both literal and non-literal meanings. Three key factors influencing this acquisition—type, metaphoricality, and context—were examined. This study recruited sixty elementary school children, divided into three age groups (7, 9, and 11 years old), along with twenty graduate students serving as an adult control group. Two truth value judgment tasks were employed: the Word-in-Sentences (WISE) task, which presents sentences containing the V-diao construction, and the Word-in-Scenarios (WISC) task, which uses stories and pictures as additional aids. The results indicated that V-diao1 was the easiest for children to comprehend, followed by V-diao2, while V-diao3 and V-diao4 were more challenging. Literal meanings of V-diao were found to be easier to acquire than non-literal ones, highlighting the metaphorical effect. Additionally, participants performed better on the WISE task than the WISC task, suggesting that contextual aids like stories and pictures did not enhance performance. These findings provide insights into the semantic development of Mandarin-speaking children and the role of metaphorical and contextual factors in language acquisition.